Allokutzneria oryzae sp. nov., isolated from rhizospheric soil of Oryza sativa L - Kannika Duangmal (2018)
IUMS. The taxonomic status of a rhizospheric soil actinomycete, designated R8-39(T), was established using a polyphasic approach. The organism had phenotypic and morphological characteristics consistent with its classification in the genus Allokutzneria. Phylogenetic analysis based on an almost complete 16S rRNA gene sequence showed that the strain formed a monophyletic clade with the type strains of members of the genus Allokutzneria. Strain R8-39(T) displayed the highest levels of 16S rRNA gene sequence similarity to Allokutzneria albata DSM 44149(T) (98.8%) and Allokutzneria multivorans YIM 120521(T) (98.3%). However, the DNA-DNA hybridization values between strain R8-39(T) and A. albata and A. multivorans were clearly below the 70% threshold. The organism was found to have chemical characteristics consistent with its classification in the genus Allokutzneria. Whole-cell hydrolysates contained meso-diaminopimelic acid, arabinose, galactose, glucose, mannose, rhamnose and ribose. The main menaquinone was MK-9(H4). No mycolic acid was detected. The G+C content of the genomic DNA was 71.8 mol%. In addition, strain R8-39(T) had a phenotypic profile that readily distinguished it from recognized representatives of the genus Allokutzneria. It is evident from the combined genotypic and phenotypic properties that strain R8-39(T) represents a novel species of the genus Allokutzneria. The proposed name for this species is Allokutzneria oryzae sp. nov.; the type strain is R8-39(T) ( = BCC 60399(T) = NBRC 109649(T)).